Letter : Spanish Relief Fund - Winstanley, E.
029-0070-001 Telegraphic address: "Wholesale Manchester" Telephone: Blackfriars 1212 Extension No. Please address your reply: Co-operative Wholesale Society Limited, Exporters, Buying and Shipping Agents, 1, Balloon Street, Manchester, 4. Cable Codes: A.B.C., 6th and 7th editions; Western Union 5 letter; Bentley Complete Phrase; Bentley Second Phrase; A.1. MARCONI, and Private. Our reference EXPORT ST/HP. 345 Your reference 22th December, 1937. The Trades Union Congress General Council, Transport House, Smith Square, LONDON. Dear Sirs, Spanish Relief Fund. We beg to confirm our telephonic conversation with you yesterday evening relative to the goods we have lying at Newcastle to your order for shipment by s.s. HARTBRIDGE. As intimated the owner has refused to allow the vessel to proceed direct to Barcelona and the Spanish Government as charterers have now arranged for the cargo to go forward to Oran for transhipment to Barcelona. In accordance with your decision we have arranged to send the goods forward in this manner and we understand that the vessel will proceed from Newcastle either tomorrow evening or Friday morning. The insurance on this transaction is of course affected, and providing the goods go forward from Oran on an approved British steamer the premium will be £10.10.0.%. We assume there will be little difficulty if the carrying steamer from Oran is French but are obtaining further information in this regard. Should the vessel be Spanish, however, the premium will be excessive and can not at the moment be estimated. We are endeavouring to obtain information regarding this point from the Spanish Embassy and will communicate with you further in this regard as early as possible. Meanwhile, we remain, Yours faithfully, E. Winstanley Export Department. 292/946/29/70